Capsaicin treatment in neuropathic pain: axon reflex vasodilatation after 4 weeks correlates with pain reduction. Issue 3 (20th March 2023) - Sendel, Manon; Dunst, Andreas; Forstenpointner, Julia; Hüllemann, Philipp; Baron, Ralf
Abstract : Pain relief after capsaicin application was associated with functional recovery of peptidergic nociceptors upon functional laser speckle contrast analysis instead of their degeneration. Abstract: Capsaicin, an agonist at the transient receptor potential vanilloid 1, is used for the topical treatment of peripheral neuropathic pain. Reversible receptor defunctionalization and degeneration and subsequent regeneration of cutaneous nociceptors are discussed as its mechanism of action. Here, we hypothesize an accelerated functional recovery of a subclass of nociceptive afferents, the peptidergic vasoactive nociceptors, as the potential cause of capsaicin analgesia. In this noninterventional exploratory trial, 23 patients with peripheral neuropathic pain were treated with one topical high-concentration capsaicin application. Baseline pain ratings, comorbidities, and quality of life were assessed. Functional laser speckle contrast analysis (heat-evoked neurogenic vasodilatation to assess functional properties of peptidergic nociceptors) and quantitative sensory testing were performed in the affected skin. Four weeks after treatment, functional laser speckle contrast analysis and questionnaires were repeated. Telephone interviews were conducted at weeks 2, 10, and 12. Topical capsaicin treatment induced a significant reduction in pain intensity with a maximum at 4 weeks. At the same time, heat-evoked neurogenic vasodilatation was on average similar to pretreatment values. Half of the patients not only showed a functional recovery but also an improvement in vasodilatation, indicating regeneration of nerve fibers. Patients with improved heat-evoked neurogenic vasodilatation at week 4 showed a greater pain reduction than those with deterioration. The degree of vasodilatation significantly correlated with pain reduction. These findings suggest that (1) regeneration of peptidergic nociceptors may be the mechanism behind capsaicin-induced analgesia and (2) that a disease-modifying effect of capsaicin on these fibers already occurs 4 weeks after application.